Optical fiber two-taper mach-zehnder interferometer as comb filter for multiwavelength laser generation - Md Ali, Mas Izyani (2016)
Critical technologies such as fiber lasers, optical filters and optical amplifiers are particularly important for the implementation of wavelength division multiplexing (WDM) systems. In order to select specific multiple lasing wavelengths in fiber laser design, a wavelength-selective comb filter is usually included in the laser cavity. In recent times, Mach-Zehnder interferometer (MZI)-based on tapered-fiber structure has received notable attention due to its benefits such as simple and low-cost fabrication, easy tuning method and relatively wide tuning range. An in-line MZI that is formed by concatenating two identical abrupt fiber tapers enhances the side mode suppression ratio (SMSR) compared to the one achieved by a single taper. In addition, the two-taper MZI structure provides a simple method to obtain optical filter with narrow linewidth. The tunability by bending and stretching mechanism are also demonstrated and discussed. It is shown that by bending the fiber, a better tuning resolution was achieved (73.0 pm/μm) compared to stretching (93.0 pm/μm) and the process was reversible for the entire range. In most cases, MZI structure is made using conventional optical fibers, which works separately from the amplifying medium. However, these two elements can be integrated together in the laser cavity by forming the MZI using the active gain medium itself. In this thesis, the author proposed a tunable dual-wavelength erbium doped ring fiber laser with tapered-EDF as comb filter. It was found that the peak power and SMSR was at the highest value when using larger taper waist diameter (33 μm). The dimension of two-taper MZI directly affects the channel spacing (free spectral range). For larger channel spacing(30.3 nm), the two-taper EDF requires shorter taper waist length (5 mm). To obtain a smaller laser linewidth (≤ 1.0 nm), the interferometer length (spacing between two tapers) must be longer (>20 mm). Based on the findings, the dual-wavelength laser can be designed to suit different applications and needs. The capability of two-taper MZI as a wavelength selector in generating multiwavelength laser in hybrid Raman- Erbium gain medium was also investigated. The ring cavity was utilized in the fiber laser setup with 1455 nm pump laser to generate stimulated Raman scattering in the range of 1555 – 1565 nm (peak gain) which overlaps with Erbium gain spectrum.The lasing efficiency is improved and leads to the generation of longer wavelength lasers. The highest number of channel count of six lasers was recorded when using output coupling ratio of 20% with 15 mm taper waist length. The average SMSR was excellent with value of 59.5 dB with -1.63 dBm average peak powers. The demonstrated multiwavelength laser showed excellent peak power and wavelength stability for two hours at room temperature with the smallest variations of less than 0.08 dB and 0.02 nm respectively.